2019
DOI: 10.1111/codi.14795
|View full text |Cite
|
Sign up to set email alerts
|

The Aortic Calcification Index is a risk factor associated with anastomotic leakage after anterior resection of rectal cancer

Abstract: Aim Anastomotic leakage (AL) is one of the most feared postoperative complications after anterior resection (AR) of rectal cancer. An adequate blood supply at the anastomotic site is regarded as a prerequisite for healing. We hypothesize that the Aortic Calcification Index (ACI) might reflect the severity of atherosclerosis in patients, and thereby be a risk factor for AL. Method AL was investigated retrospectively according to the definition of the International Study Group of Rectal Cancer in 423 rectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In colorectal surgery, the accepted leak rate is below 10% [39]. Leak rates in colorectal studies examining AC have ranged from 8 to 22% [17][18][19][20]22]. The leak rate was low at 5% among the 562 patients who underwent a primary anastomosis in this cohort.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In colorectal surgery, the accepted leak rate is below 10% [39]. Leak rates in colorectal studies examining AC have ranged from 8 to 22% [17][18][19][20]22]. The leak rate was low at 5% among the 562 patients who underwent a primary anastomosis in this cohort.…”
Section: Discussionmentioning
confidence: 95%
“…One study of patients undergoing CRC resection in Iran reported a leak rate of 20% but included only patients with ASA grades 1 or 2 in whom CVD risk is likely to be low [17]. Shen and colleagues reported a leak rate of 7.8% among 423 Chinese patients undergoing rectal cancer resection and found an independent relationship between AC and leak [22]. In addition to the lower incidence of radiographically-detectable vascular calcification in Asian populations [8], the authors highlighted the low predictive value of the AC threshold derived in this cohort, suggesting the reported relationship with leak is not directly comparable to patients from Europe and North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,12 Vascular calcification has been implicated as an independent risk factor for anastomotic leakage after esophageal and colorectal cancer surgery. 13,14 Vascular calcification might affect the blood supply of the anastomosis, 13 thus leading to anastomotic leakage. To our knowledge, there is no previous research related to vascular calcification and anastomotic leakage in gastric cancer in previously published studies.…”
Section: Introductionmentioning
confidence: 99%
“…Komen et al and Shen et al both found a correlation between aorta-iliac calcification and AL. 16,17 Vascular calcification has been investigated using computed tomography (CT) imaging software. 16 Furthermore, the assessment of vascular calcium, including local stenosis with CT scans in multiple trajectories, has been a topic of research.…”
mentioning
confidence: 99%